2,3-Dichloro-5,6-dicyano-1,4-benzoquinone (DDQ)-Mediated Tandem Oxidative-Coupling/Annulation of o-Hydroxyaryl Enaminones with Cycloheptatriene - Cheng, Dongping; Pu, Yueqi; Wang, Mingliang; Shen, Yinqiang; Shen, Jing; Xu, Xiaoliang; Yan, Jizhong (Synthesis, 2020)
A DDQ-mediated tandem reaction of easily available o-hydroxyaryl enaminones and cycloheptatriene is disclosed. It provides an effective and convenient method for the synthesis of 3-(cycloheptatrienyl)-substituted chromones in moderate to excellent yields with good functional group tolerance; this reaction involves an oxidative coupling and intramolecular annulation pathway.
Keywords: annulation; alkylation; DDQ; o-hydroxyaryl enaminones; cycloheptatriene